Dark Triad Personality Traits and Workplace Outcomes: Evidence from the Hospitality Industry - AL-RAWASHDEH, Osama Mohammad; AL MAHASNEH, Mohammad Fadel; AL NAJDAWI, Bashar M. (Journal of Environmental Management and Tourism; Vol 15 No 2 (2024): JEMT, Volume XV, Issue 2(74), Summer 2024, 2024)
The Dark Triad Personality Traits - psychopathy, narcissism, and Machiavellianism - have a significant impact on workplace dynamics. Psychopathy involves egoistic and disappointing interpersonal contact; Machiavellianism involves devious communication strategies; and narcissists use harmful tactics to gain attention and dominate teams. This study investigates the linking of DTPTs with work outcomes in the context of Jordan's hospitality sector. With the use of a standardised questionnaire, 387 hotel staff members provided quantitative data. SPSS was used to test the proposed hypotheses. Findings demonstrated that, whereas DTPTs had no effect on OCB, they do positively influence JB and TI. These results have significant theoretical and practical implications for Jordan hotels. The study recommends that to combat DTPTs in hotels, proactive measures like thorough hiring processes, investing in training programmes, and establishing clear organisational values can help. These measures can identify potential traits, foster a positive work culture, and discourage behaviours aligned with DTPTs, ultimately improving overall staff satisfaction, reducing turnover, and increasing JB.